Comparison Between Back Squat, Romanian Deadlift, and Barbell Hip Thrust for Leg and Hip Muscle Activities During Hip Extension. Issue 10 (October 2019) - Delgado, Jose; Drinkwater, Eric J.; Banyard, Harry G.; Haff, G. Gregory; Nosaka, Kazunori
Abstract : Abstract: Delgado, J, Drinkwater, EJ, Banyard, HG, Haff, GG, and Nosaka, K. Comparison between back squat, Romanian deadlift, and barbell hip thrust for leg and hip muscle activities during hip extension. J Strength Cond Res 33(10): 2595–2601, 2019—This study compared muscle activities of vastus lateralis (VL), biceps femoris (BF), and gluteus maximus (GM) during the back squat (SQ), Romanian deadlift (RDL), and barbell hip thrust (BHT) exercises performed with the same load (60 kg) and at one repetition maximum (1RM). Eight men with a minimum of 1 year's lower-body strength training experience performed the exercises in randomized order. Before each exercise, surface electromyography (EMG) was recorded during a maximal voluntary isometric contraction (MVIC) and then used to normalize to each muscle's EMG during each trial. Barbell hip thrust showed higher GM activity than the SQ (effect size [ES] = 1.39, p = 0.038) but was not significantly different from RDL (ES = 0.49, p = 0.285) at 1RM. Vastus lateralis activity at 1RM during the SQ was significantly greater than RDL (ES = 1.36, p = 0.002) and BHT (ES = 2.27, p = 0.009). Gluteus maximus activity was higher during MVIC when compared with the 60 kg load for the SQ (ES = 1.29, p = 0.002) and RDL (ES = 1.16, p = 0.006) but was similar for the BHT (ES = 0.22, p = 0.523). There were no significant differences in GM (ES = 0.35, p = 0.215) and BF activities (ES = 0.16, p = 0.791) between 1RM and MVIC for the SQ. These findings show that the RDL was equally as effective as the BHT for isolating the hip extensors, while the SQ simultaneously activated the hip and knee extensors.